2015
DOI: 10.1007/s10143-015-0669-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of subdural hematomas: dangerousness of subdural subacute hematoma

Abstract: Subacute subdural hematomas are a poorly individualized nosological entity, often equated clinically to chronic subdural hematomas. Yet, their neurological deterioration which is usually rapid seems to distinguish them from chronic subdural hematomas. We wanted to show this dangerousness by establishing the clinically evolving profile of the three types of subdural hematomas. This was a prospective and retrospective study of 63 subdural hematoma (18 acute, 13 subacute, and 32 chronic) patients admitted between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…No definition of CSDH is universally accepted [18]. Subacute SDHs were excluded from this study, because this hematoma subtype is considered to represent an entity of its own [2,12,21]. Additionally, autopsies were not performed on all of the deceased patients, and some of the causes of deaths might not be correct.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…No definition of CSDH is universally accepted [18]. Subacute SDHs were excluded from this study, because this hematoma subtype is considered to represent an entity of its own [2,12,21]. Additionally, autopsies were not performed on all of the deceased patients, and some of the causes of deaths might not be correct.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…There is currently no standard approach for the treatment of subacute subdural hematomas. 4,10,13 We previously reported that endoscopic removal of intracerebral hematomas arising from spontaneous non-vascular malformations achieved satisfactory results. 9 In this study, endoscopic removal of subacute subdural hematomas was performed.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, SASDH was considered to differ from CSDH not only based on the characteristic operative and histological findings, but also in that none of the 8 SASDH patients required reoperation. Another study by Kpelao et al 21) defined SASDH as cranial trauma between 8 and 21 days associated with isodensity on CT. In that study, SASDH did not have a neomembrane intraoperatively, unlike CSDH.…”
Section: Discussionmentioning
confidence: 99%